Design of biogas digester (Indian type) - Mohd Ayub, Adnan (2010)
This project deals with designing and fabricating a biogas digester which is focusing on Indian type. The objective of this project is to design a biogas digester that can produces biogas with specific flow rate. The digester that uses floating roof will produces constant pressure biogas. The specifications for the design will meet the type and specifications of the diesel engine that will run the generator. The fabrication of lab size digester was done by using 200 litres barrel. Biogas, a clean and renewable form of energy could very well substitute (especially in the rural sector) for conventional sources of energy (fossil fuels, oil, etc.) which are causing ecological–environmental problems and at the same time depleting at a faster rate. Utilization of biogas has gained importance in recent years, mainly due to the availability of cheap raw materials and environmental compatibility. Further, with an increase in the cost of petroleum products, biogas can be an effective alternative source of energy for cooking, lighting, food processing, irrigation and several other requirements. In essence, a biogas digester involves anaerobic fermentation process in which different groups of bacteria act upon complex organic materials in the absence of air to produce biogas. The efficiency of anaerobic digestion essentially depends on intensity of bacterial activity, which is influenced by several factors such as ambient temperature, temperature of digester material, loading rate, retention time, pH value of digester content etc. Therefore, for efficient performance of a biogas plant, it is necessary to regulate all the factors suitably. The rate of biogas production also depends on the ambient temperature of a particular region.